2022
DOI: 10.3390/f13111756
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Dynamics in a Poverty-Stricken Mountainous City: Land-Use Change, Urban Growth Patterns, and Forest Fragmentation

Abstract: For poverty-stricken mountainous cities in China, both poverty alleviation and ecological restoration projects are sources of land-use change in urban development. However, the patterns in changes are understudied in light of sustainable forest management. The study aims to explore the characteristics of land-use change in a poverty-stricken mountainous city with a focus on forests. This research proposed a three-step approach to explore the multi-aspect dynamics of land change, including the differences among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…At the macro-scale, this Special Issue discusses three aspects of forest ecosystem characteristics and management, i.e., characteristic identification [5][6][7][8], mechanism analysis [9][10][11], and optimization management [12].…”
Section: Mechanism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the macro-scale, this Special Issue discusses three aspects of forest ecosystem characteristics and management, i.e., characteristic identification [5][6][7][8], mechanism analysis [9][10][11], and optimization management [12].…”
Section: Mechanism Analysismentioning
confidence: 99%
“…The authors suggested that ecological restoration projects enhanced the main ecological function of individual regions, and conducted a detailed analysis of the impacts of the "Grain for Green" project. Wen et al (2023) [6] proposed a three-step approach to explore the multi-aspect dynamics of land change, including the differences among land-use categories, spatial characteristics of urban expansion, and forest fragmentation, and explored characteristics of land-use change in a low-income mountainous city (Enshi City, China). The findings confirmed that recent planning measures were effective in restoring the natural environment, and that the identified key areas can support sustainable forest management during urban growth.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Human activities such as agricultural farming and urbanization are important drivers of habitat quality evolution, and land use change is the most direct reflection of human activities [39][40][41], so land use transformation is one of the main factors in habitat quality. This study found that land use changes in Jiaozuo City from 1990 to 2020 were relatively drastic, mainly due to the interconversion between cultivated land and other types of land, while the expansion of construction land directly or indirectly led to an overall decline in habitat quality.…”
Section: Impact Of Land Use Change On Habitat Qualitymentioning
confidence: 99%